Factors Influencing Aggressive Adolescent Behavior: An Analysis Using the Decision Tree Method. Issue 6 (24th October 2022) - Zhang, Yu; Shi, Peipei; Gao, Mengjuan; Chang, Hongjuan
Abstract: Aggression among adolescents is a significant public health concern worldwide. To safeguard adolescents' physical and mental health, controlling the incidence of aggressive behavior and its triggers and drivers is necessary. Different risk factors in each environment drive adolescent aggression. These factors are interconnected, making the environment an ecosystem of aggression. This study aims to analyze the factors that influence adolescents' aggressive behavior and provide a basis for formulating measures to reduce such behavior in the future. This multicenter cross-sectional study was conducted in five middle schools in Lingbao City. The participants were junior high school students aged 11–15 years. Data were analyzed from January to March 2020 using the decision tree analysis method. The aggressive behavior scale, adolescent emotion regulation scale, family intimacy and adaptation scale, parental education participation scale, and a simple parenting style questionnaire were used for the investigation. Of the 581 participants, 25.5% demonstrated a tendency for aggressive behavior, while the remaining did not. The decision tree analysis showed that the incidence of adolescent aggression was the highest (54.8%) when the maternal overprotective score was greater than or equal to 17, the adolescent had low emotional control, and the mother's intelligence score was higher than 30. The decision tree model reflects the influencing factors of adolescent aggressive behavior from multiple levels and provides a reference for formulating effective intervention measures to control such behavior and its influencing factors.